Young people's emotional engagement with music videos : an exploratory study - Wilson, Johanna N. (2018)
Music serves an important psychological function during youth, particularly when it is used as a tool for regulating affect. The contexts in which youths can engage with music have changed as a result of new technology and social media sites. Music videos (MVs) have become more accessible as a result of these changes, allowing youth listeners to engage with audio-visual media from virtually anywhere. Music psychology research can benefit from a better understanding of how information from MVs affects emotional and perceptual outcomes during music listening, particularly in youth audiences. The current study aimed to investigate this underexplored phenomenon. It employed qualitative and quantitative methodologies in order to gain insight into youth experiences with MVs, as well as understand how individual differences such as healthy music use and personality contribute to these outcomes. Content analysis revealed MVs had the ability to influence emotional and perceptual outcomes, both during the MV watching episode and during subsequent audio-only listening episodes. Furthermore, statistical analyses found evidence suggesting individual differences play a role in the types of outcomes the individual experienced, however, findings from the qualitative analysis revealed other traits such as empathy and ability to show agency may also mediate the affective outcomes from MVs. Results from this study provide novel insights into the MV watching phenomenon and provides a framework for future research in the topic.